Toward futuristic near-natural collaborations on Distributed Multimedia Plays architecture - Rønningen, Leif Arne; Panggabean, M; Tamer, Özgür (The 10th IEEE International Symposium on Signal Processing and Information Technology, 2010)
This paper presents a vision of how people can collaborate in real-time in the future from different places on the continents with near-natural quality of experience. To achieve that very high quality, the requirements are also very high and challenging. The ultimate challenge for its implementation is to guarantee end-to-end delay less than 10-20 ms with graceful quality variability to enable live musical collaborations. The Distributed Multimedia Plays architecture with the AppTraNet protocol and the design of the collaboration spaces is our proposal for the realization of the vision, since existing Internet standards are unable to provide such guarantee. The relation of this novel proposal to the existing and future standards is also discussed. It is expected that significant milestones on this research avenue will be attainable in the next 5-10 years.